Diosgenin Induces Apoptosis in HepG2 Cells through Generation of Reactive Oxygen Species and Mitochondrial Pathway. (9th May 2012) - Kim, Dae Sung; Jeon, Byoung Kook; Lee, Young Eun; Woo, Won Hong; Mun, Yeun Ja
Abstract : Diosgenin, a naturally occurring steroid saponin found abundantly in legumes and yams, is a precursor of various synthetic steroidal drugs. Diosgenin is studied for the mechanism of its action in apoptotic pathway in human hepatocellular carcinoma cells. Based on DAPI staining, diosgenin-treated cells manifested nuclear shrinkage, condensation, and fragmentation. Treatment of HepG2 cells with 40 μ M diosgenin resulted in activation of the caspase-3, -8, -9 and cleavage of poly-ADP-ribose polymerase (PARP) and the release of cytochrome c. In the upstream, diosgenin increased the expression of Bax, decreased the expression of Bid and Bcl-2, and augmented the Bax/Bcl-2 ratio. Diosgenin-induced, dose-dependent induction of apoptosis was accompanied by sustained phosphorylation of JNK, p38 MAPK and apoptosis signal-regulating kinase (ASK)-1, as well as generation of the ROS. NAC administration, a scavenger of ROS, reversed diosgene-induced cell death. These results suggest that diosgenin-induced apoptosis in HepG2 cells through Bcl-2 protein family-mediated mitochndria/caspase-3-dependent pathway. Also, diosgenin strongly generated ROS and this oxidative stress might induce apoptosis through activation of ASK1, which are critical upstream signals for JNK/p38 MAPK activation in HepG2 cancer cells.